Pallaskattens (Otocolobus manul) beteende i två djurparker - påverkan av hägndesign och miljö - Fransson, Evelina (2014)
The Pallas cat is a small cat living in central Asia. The cat is approximately the size of a domestic cat but the Pallas cat is more stocky build and has a much thicker fur that enables the cat to live in a climate with temperatures plummeting to -50°C. The thick fur is one of the reasons this cat has been a popular game for hunters in the past. Nowadays there are other threats to the Pallas cat. One of the major threats today is the reduction of food sources. Pallas cats feed mostly on pikas (Ochotona dauurica) and other small animals which are thought of as pests by the humans living in the same area. Pest control reduces the Pallas cat’s food sources and thus making it harder for the cat to survive. To help to secure the Pallas cat survival the species has been included in one of the many breeding programs held in European zoos called European Endangered Species Programme (EEP). Despite a fairly good breeding success the problem of breeding Pallas cats in captivity is the low survival rate of the kittens. More than half of the kittens do not survive the first four months and examinations of the deceased kitten revile that the most common reason is the disease toxoplasmosis. Stress in captivity is something that can have an effect on the immune system and therefore could be a contributing fact for the high mortality rate. This study focuses on different aspects that can help determine the welfare of Pallas cats in captivity. Data was collected from four Pallas cats in two different zoos and both the cats’ behaviour and their space-use were recorded. The results of the study showed that there were small differences in the total number of performed behaviours in the two zoos. The cats in Nordens Ark showed a slightly higher number of behaviours than the cats in Parken Zoo. The cats used their enclosure differently in the two zoos. The design of the enclosures at Nordens Ark appeared to result in a wider use of the whole enclosure than the enclosure design at Parken Zoo. Due to the limited number of individuals included in this study and the short time during which this study was conducted it is hard to draw any definitive conclusions and more research is needed. To date there is very little known about Pallas cats and in order to maintain a good welfare for Pallas cats in captivity it is important to understand what affects their welfare so improvements can be made.